Novel horizontal and vertical integrated bioethics curriculum for medical courses - D'Souza, Russell F.; Mathew, Mary; D'Souza, Derek S. J.; Palatty, Princy (Medical teacher, 2018)
Studies conducted by the University of Haifa, Israel in 2001, evaluating the effectiveness of bioethics being taught in medical colleges, suggested that there was a significant lack of translation in clinical care. Analysis also revealed, ineffectiveness with the teaching methodology used, lack of longitudinal integration of bioethics into the undergraduate medical curriculum, and the limited exposure to the technology in decision making when confronting ethical dilemmas. A modern novel bioethics curriculum and innovative methodology for teaching bioethics for the medical course was developed by the UNESCO Chair in Bioethics, Haifa. The horizontal (subject-wise) curriculum was vertically integrated seamlessly through the entire course. An innovative bioethics teaching methodology was employed to implement the curriculum. This new curriculum was piloted in a few medical colleges in India from 2011 to 2015 and the outcomes were evaluated. The evaluation confirmed gains over the earlier identified translation gap with added high student acceptability and satisfaction. This integrated curriculum is now formally implemented in the Indian program's Health Science Universities which is affiliated with over 200 medical schools in India. This article offers insights from the evaluated novel integrated bioethics curriculum and the innovative bioethics teaching methodology that was used in the pilot program.